2020
DOI: 10.1002/dta.2895
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and robust on‐scene detection of cocaine in street samples using a handheld near‐infrared spectrometer and machine learning algorithms

Abstract: On-scene drug detection is an increasingly significant challenge due to the fastchanging drug market as well as the risk of exposure to potent drug substances. Conventional colorimetric cocaine tests involve handling of the unknown material and are prone to false-positive reactions on common pharmaceuticals used as cutting agents. This study demonstrates the novel application of 740-1070 nm small-wavelength-range near-infrared (NIR) spectroscopy to confidently detect cocaine in case samples. Multistage machine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…For a regression model, it is unlikely that a discrete 0.0% cocaine concentration is predicted for all non‐cocaine drugs and cutting agents. An adjustable cut‐off threshold on the predicted concentration is therefore applied in a similar fashion as earlier work using a near infrared (NIR)‐based model 7 . In this way, the number of FP results can be reduced by accepting a certain degree of FN results for low‐level (i.e., below threshold) cocaine samples.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For a regression model, it is unlikely that a discrete 0.0% cocaine concentration is predicted for all non‐cocaine drugs and cutting agents. An adjustable cut‐off threshold on the predicted concentration is therefore applied in a similar fashion as earlier work using a near infrared (NIR)‐based model 7 . In this way, the number of FP results can be reduced by accepting a certain degree of FN results for low‐level (i.e., below threshold) cocaine samples.…”
Section: Resultsmentioning
confidence: 99%
“…Full details of these sets are reported elsewhere. 7 Thirteen case samples provided by the Amsterdam Police Laboratory were included in this study that were identified to 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations